Assessing lactate stability at the minimum lactate steady state velocity in male trained middle-distance runners - Seyed Houtan Shahidi (PLoS ONE, 2026)
Objectives This study investigated the physiological behavior of the running velocity associated with the Minimum Lactate Steady State (vMLaSS), derived from a 6 × 800-m interval protocol, and examined whether this intensity produced stable metabolic and lactate responses during a 30-minute constant-load validation run in trained endurance runners. Methods Fifteen trained male middle- and long-distance runners completed a graded treadmill test to determine maximal oxygen uptake. Following a supramaximal sprint to induce hyperlactatemia, each athlete performed a 30-minute constant-load run at a velocity derived from the lactate-minimum approach. Following a supramaximal sprint to induce hyperlactatemia, each athlete performed a 30-minute constant-speed run at their individually determined MLaSS velocity. Blood lactate samples were collected at 10-minute intervals, and breath-by-breath cardiopulmonary variables were continuously recorded. Lactate kinetics were analyzed using a Friedman test with Wilcoxon signed-rank post-hoc comparisons ( p < 0.05). Results Blood lactate exhibited significant time-dependent fluctuations during the 30-minute trial (Friedman χ² (3) = 28.72, p < 0.001). Lactate increased sharply by minute 10, declined at minute 20, and rose again at minute 30, exceeding the classical MLSS criterion of ≤1 mmol·L ⁻ ¹ change during the final 20 minutes. In contrast, cardiopulmonary variables remained stable throughout V̇O₂ (3.43 ± 0.11 L·min ⁻ ¹; p = 0.86) and V̇CO₂ (3.21 ± 0.14 L·min ⁻ ¹; p = 0.91). Carbohydrate oxidation predominated (214.5 ± 19.3 g·h ⁻ ¹), whereas fat oxidation remained minimal (–0.9 ± 2.7 g·h ⁻ ¹). Conclusion Despite stable cardiorespiratory and substrate-utilization profiles, the significant variability in blood lactate concentration during the 30-minute constant-load run indicates that the running velocity derived from the lactate-minimum approach did not elicit a lactate steady state in this trained cohort. These findings suggest that physiological responses at the MLaSS-derived intensity may differ from classical steady-state expectations in highly trained endurance runners and highlight the need for direct MLSS verification in future studies.